Sirtuins as Potential Therapeutic Targets for Hepatitis B Virus Infection - Kong, Fanyun; Li, Qi; Zhang, Fulong; Li, Xiaocui; You, Hongjuan; Pan, Xiucheng; Zheng, Kuiyang; Tang, Renxian (Frontiers in Medicine, 2021)
Sirtuins (SIRTs) are well-known histone deacetylases that are capable of modulating various cellular processes in numerous diseases, including the infection of hepatitis B virus (HBV), which is one of the primary pathogenic drivers of liver cirrhosis and hepatocellular carcinoma. Mounting evidence reveals that HBV can alter the expression levels of all SIRT proteins. In turn, all SIRTs regulate HBV replication via a cascade of molecular mechanisms. Furthermore, several studies suggest that targeting SIRTs using suitable drugs is a potential treatment strategy for HBV infection. Here, we discuss the molecular mechanisms associated with SIRT-mediated upregulation of viral propagation and the recent advances in SIRT-targeted therapy as potential therapeutic modalities against HBV infection.